PENGARUH MODEL PEMBELAJARAN CONNECTING, ORGANIZING, REFLECTING, EXTENDING TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK - Masyithah, Masyithah (Jurnal Edukasi dan Penelitian Matematika, 2023)
Mathematics learning can be said to be achieved if students understand mathematical concepts, one of its objectives. Based on observations, class XI MIPA students at SMA Negeri 4 Bukittinggi have low understanding of mathematical concepts. Using the connecting, organizing, reflecting, extending (CORE) learning model can improve students' understanding of mathematical concepts. This model uses a discussion method to activate and develop students' thinking skills. The purpose of this study was to find out whether students who took lessons using the CORE learning model had better understanding of mathematical concepts than students who took lessons using conventional learning models in class XI MIPA SMA Negeri 4 Bukittinggi. Research methods are quasi-experimental. SMA Negeri 4 Bukittinggi's class XI MIPA students in the 2022/2023 academic year were the population of this study. Sampling was done randomly (simple random sampling), XI MIPA 1 was selected as the experimental class and XI MIPA 4 as the control class. This study used essays to test understanding of mathematical concepts. Using data analysis, it was determined that the CORE learning model affected students' understanding of mathematical concepts, students with the CORE learning model understood mathematical concepts better than students with conventional learning models at  α = 0.05.Keywords – CORE learning model,  understanding of mathematical concepts, conventional learning model.